Is Attachment Theory Consistent with Aboriginal Parenting Realities? - Neckoway, Raymond; Brownlee, Keith; Castellan, Bruno (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2007)
Attachment theory has become one of the most inﬂuential models guiding parent-child relationships in programs of prevention, treatment, and education, including programs for Aboriginal parents. However, whether the model can be reliably applied when working with Aboriginal peoples has not yet been established. Studies on attachment security conducted with different cultural groups provide a means of comparing naturally occurring differences in parenting practices and socio-emotional environments of children. These studies report inconsistencies of attachment security across cultures and suggest that consideration should be given to cultural differences when applying attachment theory across cultures. In this article, we analyse the correspondence between attachment theory and descriptions of Aboriginal parenting and question the relevance of attachment theory to Aboriginal parents who do not adhere to the mother-infant dyad as the sole contributor to the child’s sense of security.